Imitations of Life : Fannie Hurst's Gaslight Sonatas. - Ravitz, Abe C. (Southern Illinois University Press, 2009)
In the early 1920s, Fannie Hurst's enormous popularity made her the highest-paid writer in America. She conquered the literary scene at the same time the silent movie industry began to emerge as a tremendously profitable and popular form of entertainment. Abe C. Ravitz parallels Hurst's growing acclaim with the evolution of silent films, from which she borrowed ideas and techniques that furthered her career. Ravitz notes that Hurst was amazingly adept at anticipating what the public wanted. Sensing that the national interest was shifting from rural to urban subjects, Hurst set her.